Lobophorin Producing Endophytic Streptomyces olivaceus JB1 Associated With Maesa japonica (Thunb.) Moritzi & Zoll. - Um, Soohyun; Lee, Jaeyoun; Kim, Seung Hyun (Frontiers in Microbiology, 2022)
In this study, we focused on endophytes of Maesa japonica (Thunb.) Moritzi & Zoll. and the plant-microbe interaction at metabolite levels. We isolated seven endophytes associated with M. japonica (JB1-7), and focused on Streptomyces olivaceus JB1 because of antibacterial activities of its secondary metabolites. We confirmed lobophorin analogues production from the bacterial strain JB1 by using spectroscopic techniques such as NMR, UV, and LC-Q-TOF-MS. In the LC/MS system, thirteen reported lobophorin analogues and twelve unreported analogues were detected. Among metabolites, lobophorin A was clearly detected in the dried foliar residues of M. japonica which implies that JB1 resides in the host and accumulates its secondary metabolites likely interacting with the plant. Antimicrobial activity tests of the secondary metabolites against undesirable contaminants isolated from the external surface of M. japonica supported the host and microbe mutualistic relationship. In the meantime, lobophorin producing Streptomyces spp. were isolated from marine environments such as marine sediments, algae, corals, and sponges. As lobophorin producing Streptomyces is isolated commonly from marine environments, we conducted a saline water stress tolerance test with JB1 showing saline medium does not accelerate the growth of the bacterium.